1999
DOI: 10.1164/ajrccm.160.1.9806048
|View full text |Cite
|
Sign up to set email alerts
|

Initial Microbiologic Studies Did Not Affect Outcome in Adults Hospitalized with Community-Acquired Pneumonia

Abstract: Microbiologic studies (MBSs) fail to identify a specific pathogen in more than 50% of patients with community-acquired pneumonia (CAP). The 1993 American Thoracic Society guideline (ATS-GL) for the management of CAP advised selecting initial antibiotic regimens based on severity of illness and comorbidities. Our study evaluated the role of initial MBS in adult patients hospitalized with CAP and treated according to the ATS-GL. In 184 patients hospitalized at our facility for CAP in 1996, and treated according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 8 publications
3
59
1
7
Order By: Relevance
“…No study has shown that initial microbiological studies affect outcome [59]. Nevertheless, many clinicians feel that microbial investigation may be of help in guiding treatment, particularly in the more severely ill patients.…”
Section: Microbiological Investigationmentioning
confidence: 99%
“…No study has shown that initial microbiological studies affect outcome [59]. Nevertheless, many clinicians feel that microbial investigation may be of help in guiding treatment, particularly in the more severely ill patients.…”
Section: Microbiological Investigationmentioning
confidence: 99%
“…15 In general our findings are supportive of literature showing that sputum samples have little overall impact upon practical management of patients. [2][3][4]16,17 Prior to our intervention approximately 13% of sputum samples (45/347) appeared to lead to a change in management, but half of these samples were 'inappropriate'. Even fewer samples (around 3%, 4/133) directly altered prescribing after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that sputum sampling has low sensitivity, specificity and impact on treatment decisions. [1][2][3][4] Ideally antibiotic treatment should be tailored to the causative pathogen but at presentation the aetiology is rarely known, and patients therefore commonly receive empirical, often broad-spectrum antibiotics. …”
mentioning
confidence: 99%
“…17,41,42 The test is often unhelpful, as positivity becomes evident no earlier than 24 hours after obtaining the specimen, and results typically have little influence on therapeutic decisions and outcomes. 41,[43][44][45] However, a review of patients with confirmed pneumococcal pneumonia found that 42% of patients with positive blood culture results had their treatment changed as a result. 46 As the overall prevalence of β-lactam resistance remains low in the UK, rapid near-patient testing for pneumococcal infection could influence therapeutic decisions.…”
Section: Diagnostic Tests For Streptococcus Pneumoniaementioning
confidence: 99%